CYP2D6*10 polymorphism and the enantioselective O‐desmethylation of S‐(+)‐ and R‐(‐)‐venlafaxine in Japanese psychiatric patients. Issue 5 (9th February 2021) - Sasaki, Taro; Yasui‐Furukori, Norio; Komahashi‐Sasaki, Hazuki; Shinozaki, Masataka; Hayashi, Yuki; Kato, Kazuko; Inoue, Yoshimasa; Tsuchimine, Shoko; Watanabe, Takashi; Sugawara, Norio; Shimoda, Kazutaka
Abstract: According to previous studies, R‐(‐)‐venlafaxine (VEN) has higher enantioselectivity than S‐(+)‐VEN, and the plasma concentration of R‐(‐)‐VEN varies depending on CYP2D6 activity. Therefore, we examined the pharmacokinetic effects of CYP2D6*10 genotypes on the steady‐state concentrations of the enantiomers of VEN. The individuals were 71 Japanese depressed patients treated with racemic VEN. The concentrations of the enantiomers of VEN and O‐desmethylvenlafaxine (ODV) were measured. Polymerase chain reaction (PCR) was used to determine the CYP2D6*10 genotypes. The plasma concentrations of S‐(+)‐VEN were approximately 1.9‐fold higher than those of R‐(‐)‐VEN. The plasma concentrations of S‐(+)‐VEN and R‐(‐)‐VEN seemed to be higher in individuals with two mutant alleles of CYP2D6*10, although no significant differences were found in the plasma levels of S‐(+)‐VEN and R‐(‐)‐VEN between CYP2D6*10 genotypes. The number of mutant alleles of CYP2D6*10 was a significant factor associated with the R‐(‐)‐ODV/R‐(‐)‐VEN ratio ( P  = .004) in multiple regression analysis. This suggests that CYP2D6*10 mutations affect the metabolism of R‐(‐)‐VEN and S‐(+)‐VEN. Further studies are needed to examine how these findings affect clinical practice.